Analysis Using the American Productivity Center (APC) Method Case Study UD. Tempe Mawar Indah - Muhammad Firdaus; Yana, Dewi; Andriani, Meri (JURUTERA - Jurnal Umum Teknik Terapan, 2023)
A company's competitive ability is not only measured by the superiority of its products, but also by the performance of its industrial system as a whole which is reflected in the profits earned, so that it can be used for the development of its business and workforce through industrial effectiveness, as well as continuous quality improvement. Increased productivity is expected to increase the development and progress of the company. UD. Tempe Mawar Indah does not have detailed knowledge about how the company develops and improves. So it is necessary to evaluate the productivity of the company. The method used in analyzing company productivity is the American Productivity Center (APC) and productivity evaluation uses the Productivity Evaluation Tree (PET) method. The results obtained from this study are the Total Productivity Level at UD. Tempe Mawar Indah Period I (Basic) was 127.58 then in Period II it decreased to 116.88 (-10.7), also caused by increased use of resources compared to production. In Period III it also decreased again to 114.35 (-2.53), also caused by increased use of resources compared to production. As a productivity evaluation that has been carried out using the PET method, namely increasing productivity in Period III with a scenario of reducing input by 4.18% or (Rp.27,601,350) so that productivity in Period III increases to 1.19%.